Phenolic profiles differentiate wild bilberry and cultivated blueberry fruit - Hellström, Jarkko; Karhu, Saila; Karhu, Jouni; Järvenpää, Eila; Välimaa, Anna-Liisa (Elsevier, 2024)
The dark fruit of European wild-grown blueberry known as common bilberry (Vaccinium myrtillus L.) is associated with many health-promoting properties and has a steadily growing global market, especially in the food supplement sector. The adulteration of bilberry products with some less expensive fruits and berries with an intense color is a well-known problem. Phytochemical profiling is a viable option to discern different plant species from each other. In this study, the chemical composition of the fruit of wild bilberry and its close relative, cultivated blueberry (Vaccinium sp.), were analyzed and compared. A large number of samples of different geographical origin was collected. The major phenolics, including anthocyanins, chlorogenic acid, and condensed tannins, were determined by liquid chromatography using various detection methods. Significant differences were found in the phenolic profiles between wild-grown bilberry and cultivated blueberry. Principal component analysis indicated that it was possible to distinguish bilberry from cultivated blueberry based solely on their anthocyanin or tannin profiles. However, the geographical origin of the berries could not be identified according to their phenolic compound composition.
Keywords: tannin; Vaccinium; anthocyanin; authenticity; chemical fingerprinting